PEMANFAATAN MEDIA BERBASIS LINGKUNGAN DAN MEDIA STANDAR LABORATORIUM PADA PEMBELAJARAN DASAR-DASAR SAINS DI PROGRAM STUDI PENDIDIKAN KIMIA FTK UIN AR-RANIRY - Azhar Azhar (Lantanida Journal, 2016)
In learning science should be strived to be easier in the learning process, especially on the basic concepts of science that had been considered as the cause of difficulties for students to understand the concept of advanced science. One way to make it easier to recognize the learning materials of science is to utilize tools, materials and objects as a learning medium that is in accordance with the learning materials and experiences of learners. To be able to utilize the existing media in the environment, educators and learners must identify the characteristics of the object or event they have, then adjust the characteristics of its existence on the object or event to be studied. The media used should be familiar with the students as well as in accordance with the ability of educators in operating it. The purpose of this research is to examine the difference of learning outcomes of FTK Chemistry Education UIN Ar-Raniry on learning basic science that is applied with the utilization of environment-based media compared to the use of laboratory standard media applied. This study used experimental quasi-experimental design with a pretest-postest control-group design. In accordance with the hypothesis to be tested then in this study set two research groups are experimental groups and regular groups. Based on the result of research known that from distribution list F with df = 1,58 at significant level = 0,05 obtained F (0,05) (1,58) = 4,01 while Fvalue is known = 18,63. So it can be concluded that the value of Fvalue> Ftable, means the proposed research hypothesis accepted. Thus show that the result of study of FTK Chemistry Education Student Program UIN Ar-Raniry by using environment-based media compared to using standard media laboratory on learning basics of science.